The Effectiveness of ClassPoint Media in Improving Communication Skills of Fifth-Grade Elementary School Students - Apriani, Yohana; Wuryastuti, Sri; Hanif, Muhammad (Universitas Sebelas Maret, 2023)
Not all elementary school students possess good communication skills, necessitating the use of a learning medium to enhance their abilities. One such medium that may be employed is ClassPoint media. This research was conducted to determine the effectiveness of ClassPoint learning media in improving the communication skills of fifth-grade students at SDN Total Persada. The study utilized a quantitative research approach, specifically employing a pre-experimental design with a single group pre-test and post-test. The researchers employed a purposive sampling strategy to gather a study sample consisting of 28 students from fifth grade C. The data were obtained by observing full observers by two researchers (raters) and documentation. The observation sheet consisted of 25 observations and had been declared fit for use by experts. The Cohen's Kappa test was used to assess the level of Inter-Rater Reliability (IRR). The pre-test findings yielded values of 0.875 and 0.872 in the post-test, indicating a high degree of agreement, approaching perfection. The data analysis methods employed in this study encompassed descriptive statistics and parametric inferential statistics. To ensure the validity of the parametric tests, normality and homogeneity tests were conducted. Additionally, paired sample t-tests and One-way ANOVA testing were used to examine the relationships and differences among the variables of interest. The paired sample t-test and the One-Way ANOVA test yielded a significance value of 0.000, which is less than the predetermined alpha level of 0.05. As a result, the alternative hypothesis (Ha) was accepted, whereas the null hypothesis (Ho) was rejected. Consequently, a notable enhancement in the effectiveness of ClassPoint educational technology was seen in relation to the development of communication skills among fifth-grade students at SDN Total Persada. This study has the potential to offer up-to-date information and insights for educational institutions, schools, instructors, and readers in the elementary school setting.